Libel by the numbers: The use of public opinion polls in defamation lawsuits. Issue 2 (3rd July 2017) - Robinson, Eric P.
Abstract: After a rocky start, polls became ubiquitous in the twentieth century in a variety of fields. However, the courts generally resisted accepting polls and other social science evidence until the early 1950s, on the grounds that they were hearsay. But while social scientists understand reputation in a variety of ways, the law sees an individual's reputation as a social phenomenon. This makes the opinions of others an inherent part of the legal claim of defamation, and polls an obvious type of evidence in such cases. But use of polling evidence in defamation cases remains rare. This article examines courts' acceptance of polling data as evidence in defamation cases, including the actual cases in which it has been used as evidence, and concludes with recommendations on how defamation litigants and courts considering defamation cases can use such evidence.